The Folk Music Instrument Identification, Ocarina as An Example - Krzysztof TYBUREK (Communications of International Proceedings, 2021)
Thanks to a particular analysis of the audio waveform, we can determine the source of the signal and qualify it to the appropriate class of objects. This issue concerns various classes of sounds - also derived from musical instruments. By extracting the physical features of the signal, we obtain information about the structure of the instrument that is the source of the sound. Different values of the features will describe the brass and other wooden instruments. This is due to the construction and materials used in the manufacture of the instrument. The conducted experiments refer an attempt to parameterize the ocarina instrument, which is a folk musical instrument from the group of aerophones. The aim was to compare the values of the physical features of the ocarina sound (read in the time and frequency domains) with descriptors obtained from the soprano saxophone, flute and tuba. Alto Ceramic Sweet Potato Ocarina was intended for research. The sample population for each instrument was 21.
Keywords: Ocarina; Timbre; Power Spectrum; MFCC; Timbre; Power Spectrum; Music Instrument Identification; MPEG 7